THE INFLUENCE OF LIVE VIDEO STREAMING, TRUST, AND PRICE FEATURES ON PURCHASING DECISIONS FOR TIKTOK E-COMMERCE CUSTOMERS - Rini Hardiyani (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims (1) To determine the effect of live video streaming on e-commerce purchasing decisions on TikTok. (2) To determine the effect of Trust on e-commerce purchasing decisions on TikTok. (3) To determine the effect of price on e-commerce purchasing decisions on TikTok. The research method used is a quantitative method. Data collection is used in this study using a questionnaire (google form). The number of samples in this study was calculated using the Slovin formula and obtained 96 respondents who were TikTok e-commerce users. The data processing method in this study used SPSS software version 20.0. The results of the study showed that (1) Live Video Streaming has a significant effect on Purchasing Decisions. (2) Trust does not have a significant effect on Purchasing Decisions. (3) Price has a positive effect on purchasing decisions.